English Literacy-Based Study Group for Community Empowerment in Mata Air Village - Daniel Frengki Kamengko; Mesri W.N Man; Jeremia A. Wewo (LP2M INSURI Ponorogo, 2025)
Creating an English literacy-based learning group in Mata Air Village, Regency, is the main objective of this project. The pressing issue being addressed is the low English proficiency of locals, which prevents them from communicating effectively with tourists and restricts their involvement in the tourism industry. This program aims to improve community members' proficiency in English so they can interact with tourists more successfully and take advantage of greater economic opportunities. The techniques that promote a collaborative learning environment include project-based training, cooperative learning, and interactive workshops reflecting community devotion and empowerment. According to preliminary findings, participants' confidence in their language use has grown, and their interest in tourism-related activities is increasing. The results emphasize how crucial language literacy is to strengthening community empowerment and encouraging sustainable tourism growth in the area.